2020
DOI: 10.1093/ofid/ofaa534
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Acute Respiratory Syndrome Coronavirus 2 Infection in Hospital Workers: Results From a Screening Study in New Jersey, United States in Spring 2020

Abstract: Background SARS-CoV-2 infection is a critical concern among health care workers (HCW). Other studies have assessed SARS-CoV-2 virus and antibodies in HCW, with disparate findings regarding risk based on role and demographics. Methods We screened 3,904 employees and clinicians for SARS-CoV-2 virus positivity and serum IgG at a major New Jersey hospital from April 28-June 30, 2020. We assessed positive tests in relation to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
7
22
1
Order By: Relevance
“…The input training vectors V(i,j) are the [antibody(i) concentration/ cut-off level(i)] of the sample i, where i = 1: 3 assays, and j = 1: number of samples. Each vector was labeled with one of the three phases of the disease: infection phase (visit 1), inflammation phase (visits 2–4) and recovery phase (visits 5–11) 32 , as shown in Fig. 4 A.…”
Section: Methodsmentioning
confidence: 99%
“…The input training vectors V(i,j) are the [antibody(i) concentration/ cut-off level(i)] of the sample i, where i = 1: 3 assays, and j = 1: number of samples. Each vector was labeled with one of the three phases of the disease: infection phase (visit 1), inflammation phase (visits 2–4) and recovery phase (visits 5–11) 32 , as shown in Fig. 4 A.…”
Section: Methodsmentioning
confidence: 99%
“…Not surprisingly, among HCW, patient-facing staff are more likely to test positive. 4 , 5 A few studies have suggested a dose-response relationship, observing higher rates of infection among HCW caring for a greater number of patients with suspected or confirmed COVID-19. 5 , 6 A notable exception is lower rates of infection among HCW in Intensive Care Units (ICUs).…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 A few studies have suggested a dose-response relationship, observing higher rates of infection among HCW caring for a greater number of patients with suspected or confirmed COVID-19. 5 , 6 A notable exception is lower rates of infection among HCW in Intensive Care Units (ICUs). While HCW in ICUs provide care for suspected or confirmed COVID-19 positive patients, and therefore may have the highest workplace exposure to COVID-19, several studies have documented lower rates of infection compared to other HCW with less exposure.…”
Section: Introductionmentioning
confidence: 99%
“…To date, nosocomial infection by COVID-19 has been discovered and reported in numerous healthcare facilities on a global scale; however, concise analysis of nosocomial clusters is limited. [1][2][3] In this study, we clari ed the characteristics and impact of nosocomial clusters that occurred in Kyoto City in the rst year of the pandemic in order to examine preventive measures.…”
Section: Introductionmentioning
confidence: 99%